Struktura kompaktní kosti a způsob namáhání dlouhých kostí clovĕka - Hert, J; Fiala, P; Petrtýl, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 1993)
The authors elaborated a new macroscopic method which made it possible to analyze the orientation of osteons in the entire diaphysis. All long bones of the human extremities were thus analyzed. In each bone the osteons are arranged in a specific pattern but according to a uniform plan. Most of them are oriented in an oblique direction and are arranged as two helices of opposite directions located on opposite sides of the bone. The two fields are separated by a sharp borderline. Biomechanical analysis revealed that the orientation of the osteons is consistent with the direction of the maximal principal stress which depends on the normal and torsional stress to which the bone is exposed. From the orientation of osteons the authors derived ex post the mode of dominant loading of all long bones: the femur is exposed to bending in the medial direction and to outer rotation, the tibia is exposed to bending in dorsal direction and to inner rotation. The humerus is bent in the medial direction, the radius in the dorsal one. Both these bones are exposed to loading in inner rotation. In the ulna and fibula the mode of stress could not be assessed by the authors' method. The results are summarized in two diagrams which indicate the orientation of osteons and the way in which the long bones in man are exposed to load. The authors discuss the theoretical and practical impact of these findings.
Keywords: mechanický stres; Bone and Bones; kosti a kostní tkáň; In Vitro Techniques; Humans; techniky in vitro; Stress, Mechanical; lidé